The research-teaching nexus from the Portuguese academics’ perspective: a qualitative case study in a school of social sciences and humanities - Farcas, D.; Bernardes, S. F.; Matos, M. (Higher Education, 2017)
This paper reports on a study conducted as part of an action-research project—INTEGRA I&E—aiming to promote the research and teaching (R&T) nexus at the School of Social Sciences and Humanities of a Research University in Lisbon, Portugal (Instituto Universitário de Lisboa, ISCTE-IUL). This study set out to investigate a multi-informant perspective of the academics’ rhetoric (conceptions, perception of barriers/facilitators and consequences) concerning the nexus, which can be considered at different levels of the curricular and organizational structure. Focus groups were conducted with 26 professors and 8 researchers from six different disciplinary areas and, afterwards, recorded and transcribed. A content analysis was used to categorize and quantify participants’ responses. Four themes emerged: practices linking R&T, barriers, facilitators and consequences of the nexus. Different levels of analysis were identified for each theme, namely, the level of ISCTE-IUL, Research Centers, Departments, Courses and Classes. Some disciplinary differences were also encountered. This study contributes with a multi-informant and multi-level perspective of academics’ conceptions of the R&T nexus in a Portuguese research-oriented university.